KONFLIK AGRARIA DI INDONESIA - Ahmad Zuber (Jurnal Sosiologi Reflektif, 2013)
This article describe agrarian conflict in Indonesia. Until this moment many agrarian conflict are happen in Papua, Java, Kalimantan and Sumatera. This conflict consist many interests and there isn’t equity policy to society are following this conflict. The implication the agrarian conflict become latent conflict. It usually make huge damage in society and nation.